2019
DOI: 10.3389/fsurg.2019.00069
|View full text |Cite
|
Sign up to set email alerts
|

The Tensile Strength of Full-Thickness Skin: A Laboratory Study Prior to Its Use as Reinforcement in Parastomal Hernia Repair

Abstract: Purpose: Parastomal hernia is a common complication of an enterostoma. Current methods of repair have high recurrence rates and are associated with severe complications. Autologous full-thickness skin as reinforcement may reduce the recurrence and complication rates. This study aims to investigates the tensile strength of full-thickness skin; information that is essential if we are to proceed with clinical trials on humans.Methods: Full-thickness skin samples from 12 donors were tested for tensile strength, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In the literature it is reported that the mechanical properties of the skin vary in strength in the range of 0.1 to 32 MPa and the strain ratio at fracture point varies in the range of 0.42 to 2.26 [ 43 , 44 ]. Therefore, it is necessary for the materials proposed for skin regeneration to retain properties that are reliable with those of the skin.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature it is reported that the mechanical properties of the skin vary in strength in the range of 0.1 to 32 MPa and the strain ratio at fracture point varies in the range of 0.42 to 2.26 [ 43 , 44 ]. Therefore, it is necessary for the materials proposed for skin regeneration to retain properties that are reliable with those of the skin.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to introduce the concept of intra-abdominally placed autologous FTSG, to ensure that it is technically possible to perform, and that the method has no major method-related complications. Animal studies and in vitro mechanical experiments preceded this pilot application in humans; a link in a chain of studies aiming to evaluate the use of FTSG in parastomal repair and to compare the method with those currently available [ 15 , 16 ].Considering the lack of major method-related complications we conclude that this FTSG method is feasible. The results of the study along with previous preclinical experiments provide enough evidence to proceed with this novel method in a larger clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model showed good FTSG survival in both onlay and intraperitoneal positions in the abdominal wall [ 15 ]. We also conducted experiments on fresh skin samples showing that skin has remarkable tensile strength—an important property for reinforcement material in hernia surgery [ 16 ]. Histological studies from the 1930s showed no signs of malignant transformation or cyst formation related to burying full-thickness skin in humans [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current commercially-available and commonly used fibrin glue, TISSEEL, with a mechanism inspired by clotting with two components, thrombin and fibrinogen, 12 might not be sufficient for the fixation of ECM based grafts. Various kinds of absorbable or non-absorbable sutures, [13][14][15][16][17][18] staples 19 and adhesive tapes were available for fixation of grafts or medical devices such as skin grafts, vascular grafts and cardiac grafts. However, sutures and staples are limited in damaging surrounding tissues, eliciting inflammatory responses, scar tissue formation and possible anesthetics administration.…”
Section: Introductionmentioning
confidence: 99%